Jeunes Européens à Dakar et Ouagadougou. De nouvelles aventures migratoires ? - Sylvie Bredeloup (EchoGéo)
Young educated Europeans increasingly consider career scenarios in which capital cities in sub-Saharan Africa play a decisive role in their professional and personal trajectories. Based on life stories collected in Dakar and Ouagadougou, this paper examines the imaginaries, professional strategies and life projects of these young European migrants who have been recruited as interns or volunteers in international organizations or had created their own activities.